(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
This study assessed the attitude of Colleges of Education students toward sex education in Southwest Nigeria, focusing on the influence of gender, religious beliefs, parental education, and school location on their perceptions. A descriptive survey design was used to collect data from students in selected colleges of education. The study’s population included 34,274 students across 12 Colleges of Education in Southwest Nigeria. A sample of 900 students was selected using a multistage sampling technique. In the first stage, three states were randomly chosen. In the second stage, one Federal and one State College were selected from each state using stratified random sampling. Finally, 75 students from each college were purposively selected. Data was gathered using a self-developed instrument, the "Students Attitude Towards Sex Education Questionnaire" (SATSEKQ), designed to assess students’ attitudes. The instrument was validated by subject experts, and a reliability coefficient of 0.81 was obtained. The SATSEKQ was administered to the selected students through face-to-face distribution during scheduled lecture hours, with respondents assured of confidentiality and voluntary participation. Descriptive statistics, including percentage and mean, were used to answer the research questions. Path analysis tested the research hypotheses at a 0.05 significance level. The findings indicated that College of Education students generally hold positive attitudes toward sex education. However, religious beliefs and gender differences significantly shaped their attitudes. Students from religiously conservative backgrounds held more restrictive views, while female students demonstrated greater engagement with sex education than their male counterparts. Parental education and school location were found to have minimal influence on students’ attitudes. Based on these findings, it is recommended that schools develop sex education programs that respect religious beliefs while promoting comprehensive and accurate information. Teachers should tailor their methods to address gender differences, and the government should offer professional development on sensitive topics for educators.